KESTABILAN MODEL PETRI NET DARI SISTEM PEMBAYARAN TAGIHAN LISTRIK PT. PLN (Persero) RAYON AMBON TIMUR - Sya'diyah, Zumrotus (PATTIMURA UNIVERSITY, 2021)
This research develops the previous one of the electricity bill payment system in PT. PLN (Persero) Rayon East Ambon modelled by Petri Net. The previous researcher had built the Petri Net model of this payment system. In this research, we determine whether the system modelled before is stable or not. This stability will be analysed using the Lyapunov stability theory related to the Petri Net. The result shows that the electricity bill payment system modelled by Petri Net before is not stable but can be stabilized. This can be caused there is a transition which is ‘always enable’ in the modelled which is built. This research also performs a stable model of Petri Net that represents the electricity bill payment system with deleting the ‘always enable’ transition